Textile Wastewater Treatment Using Polypyrrole/Polyphenol Oxidase Membranes - Anceu Murniati; Nadia Annisa Fajriana; Gilang Adi Nugraha; Restu Muchammad Ibrahim; Arie Hardian; Buchari Buchari; Suryo Gandasasmita; Zeily Nurachman (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
Polypyrrole (PPy) is widely regarded as a useful electrode material because it has the advantages of low cost, high electrical conductivity, and thermal stability. This study aimed to synthesize PPy membranes using polyphenol oxidase (PPO) isolated from white oyster mushrooms as a biocatalyst for processing textile wastewater. The membranes were produced through the electropolymerization of pyrrole (Py) using the electrodeposition method. The raw materials comprised 0.05 M Py and crude PPO white oyster mushroom extract at 35% v/v in citrate buffer pH = 6.8. The electrolysis process was performed at 6.00 V and 1.063–1.142 A using 16.57-48.97% immobilized PPO in PPy, PPO activity of 1.640–4.160 U, and 0.35 mM phenol as a substrate. The results showed that the use of the membrane in textile wastewater with a discontinuous flow caused a decrease of pH by 14.86%, phenol by 6.80%, Chemical Oxygen Demand (COD) by 81.30%, Biological Oxygen Demand (BOD) by 78.25%, and Total Suspended Solids (TSS) by 20.65%. Meanwhile, using the sample with a continuous flow caused a decrease of pH by 23.97%, phenol by 26.09%, COD by 88.50%, BOD by 78.00%, and TSS by 65.70%. The physical performance of membrane application to textile wastewater with discontinuous (flow rate = 48.19–51.50 L/h, flux = 3191.6–3387.5 L.m-2.h-1, and permeability = 319.2–338.7 Lm-2.h-1.bar) and continuous flow (flow rate = 48.19 L/h, flux = 3191.6 Lm-2.h-1, and permeability = 319.2 Lm-2.h-1.bar) was also assessed in this study. The Scanning Electron Microscopy (SEM) image was used to assess the morphology of the membrane before and after its application.